Computational Investigation on Cracking Behaviors of AerMet 100 - Hongbo Zhang; Dayong Hu; Kangpei Meng (Metals, 2022)
AerMet 100 exhibits excellent mechanical properties, proven in previous studies; however, defects may greatly influence the mechanical behavior during the service of the material, which serves as one of the major challenges in the wider application of the material. To quantify the crack evolution process, the in-plane type I crack propagation behavior is comprehensively investigated based on the extended finite element method (XFEM). The crack growth is characterized in terms of the extracted crack propagation angle, stress intensity factor (SIF) in the crack tip, and stress field profiles during the crack propagation process. An extrapolation method is adopted to calculate the SIF, followed by a series of parametric studies on the influence of the governing factors, i.e., initial crack length, initial crack location, initial crack angle, and the crack number through numerical investigation. It is found that the crack propagation angle enlarges monotonously with the increase of the initial crack location, the initial crack length, and the crack number, increases slowly with the growth of initial crack angle, and rapidly enlarges in reverse at about 45°. The SIF in Mode I, KId, gradually decreases with the increase of the initial crack location and the crack number, and nearly keeps steady when the initial crack length and initial crack angle varies. Results provide further understanding of the failure and fracture behavior of AerMet 100 and guide the future application and design of the structures.